Examining the relationship between preschool teachers' emotional intelligence levels and their coping responses to stress - İlknur Tarman; Esin Filiz (Journal of Pedagogical Research, 2023)
Using a relational survey design, this study examined the relationship between preschool teachers' emotional intelligence levels and their coping responses to stress. A total of 257 preschool teachers from public and private institutions in Istanbul participated in the study. Demographic information form, Schutte Emotional Intelligence Scale-33-Tr (EIS), and Coping Responsive Inventory (CRI) were used to collect data. The results showed that preschool teachers' scores on the EIS and the CRI were not significantly affected by their age, education level, type of institution, or length of service. A positive and moderately significant relationship was found between teachers' EIS scores and their CRI total scores, as well as sub-scores for problem-solving, positive reappraisal, logical analysis, and seeking professional support. The EIS and the subscale of seeking environmental support in CRI, however, had a positive and low-level significant relationship.